2006
DOI: 10.1136/jcp.2005.031997
|View full text |Cite
|
Sign up to set email alerts
|

Rectal adenocarcinoma with oncocytic features: possible relationship with preoperative chemoradiotherapy

Abstract: Background: The introduction of preoperative chemoradiation into the treatment protocol of rectal adenocarcinomas has affected the microscopical morphology in subsequent resection specimens. The constellation of histopathological changes is varied and well documented. Aim: To describe oncocytic change in rectal cancers that have been treated with chemoradiation before surgery. Methods: 7 of 54 patients with rectal cancer were identified with a history of chemoradiation, specifically directed to the rectal tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Characteristic treatment induced changes within the residual tumour include attenuation of glands, increased cytological atypia, degenerative nuclear changes and decreased mitotic activity 8. Cytoplasmic vacuolation and eosinophilia have been described in rectal adenocarcinomas after therapy, and the latter appearances may reflect an endocrine or oncocytic phenotype 9 10. Stromal changes that commonly follow treatment include fibrosis, dystrophic calcification, atypical fibroblasts and vascular obliteration.…”
mentioning
confidence: 99%
“…Characteristic treatment induced changes within the residual tumour include attenuation of glands, increased cytological atypia, degenerative nuclear changes and decreased mitotic activity 8. Cytoplasmic vacuolation and eosinophilia have been described in rectal adenocarcinomas after therapy, and the latter appearances may reflect an endocrine or oncocytic phenotype 9 10. Stromal changes that commonly follow treatment include fibrosis, dystrophic calcification, atypical fibroblasts and vascular obliteration.…”
mentioning
confidence: 99%
“…Twenty-four of 28 cases reported by Ambrosini-Spaltro et al [18] and 5 of 7 cases described by Rouzbahman et al [19] showed rectal adenocarcinomas with oncocytes being the dominant cell type. Most pretreatment biopsies in the former study contained variable numbers of oncocytes [18], and we noted that oncocytes are present in most rectal cancers we examined [19]. It is reasonable to postulate that oncocytes are resistant to and survive chemoradiation, remaining as the dominant tumor cells in residual rectal cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Oncocytic rectal adenocarcinomas have thus far been documented in 2 clinical contexts: 2 series describing oncocytic rectal carcinomas in resection specimens with the patients having received preoperative chemoradiation [18,19] and 2 separate case reports documenting the occurrence of oncocytes in patients without preoperative chemoradiation [20,21].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations